GAMBARAN PH SALIVA TERHADAP KARIES GIGI PADA SISWA/I KELAS IV SD NEGERI 065015 KEMENANGAN TANI MEDAN TUNTUNGAN - sri junita nainggolan (Poltekkes Kemenkes Medan, 2016)
pH is the level of acidity or base which is measured by using pH scale from 0 to 14 in which the lower the pH is, the more the acid in solution, and the higher the pH is, the more the base in solution. In ph 7, there is no acidity or base in solution which is called neutral. The objective of the research was to find out the description of pH Saliva and caries in Grade IV students at SD Negeri 065015 Kemenangan Tani, Medan Tuntungan, in 2016. The data were gathered by conducting direct examination on the respondents. The research was descriptive; it was conducted from Februariy until June. The population was 36 Grade IV students at SD Negeri 065015 Kemenangan Tani, Medan Tuntungan, in 2016. The result of the research showed that 17 respondents (47,2 %), had acid pH saliva, 7 respondents (19,4 %), had neutral pH, and 12 respondents (33,3%) had base Ph. 42 respondents had acid ph caries with the mean of 2,42, 6 respondents had neutral pH caries with the mean of 0,9, 19 respondents had base pH caries with the mean of 1,59, and 1 respondents was free from caries that had neutral pH. The conclusion was that Grade IV students at SD Negeri 065015 Kemenangan Tani, Medan Tuntungan had high acid pH and high caries.